Effects of calcium salts of soybean oil on factors that influence pregnancy establishment in Bos indicus beef cows - Cooke, Reinaldo Fernandes [UNESP]; Cappellozza, B. I.; Guarnieri Filho, T. A. [UNESP]; Depner, C. M.; Lytle, K. A.; Jump, D. B.; Bohnert, D. W.; Cerri, R. L. A.; Vasconcelos, José Luiz Moraes [UNESP] (Amer Soc Animal Science, 2014)
The objective of this experiment was to compare fatty acid (FA) concentrations in plasma and reproductive tissues as well as hormones and expression of genes associated with pregnancy establishment in beef cows supplemented or not with Ca salts of soybean oil (CSSO) beginning after timed AI. Ninety nonlactating multiparous Nelore (Bos indicus) cows were timed inseminated on d 0 of the experiment and divided into 18 groups of 5 cows/group. Groups were randomly assigned to receive (as-fed basis) 100 g of a protein-mineral mix plus 100 g of ground corn per cow daily in addition to 1) 100 g/cow daily of CSSO (n = 9) or 2) 100 g/cow daily of kaolin (CON; rumen-inert indigestible substance; n = 9). All groups were maintained in a single Brachiaria brizanta pasture (24 ha) with ad libitum access to forage and water. However, groups were segregated daily and offered treatments individually at the working facility during the experimental period (d 0 to 18). Blood samples were collected and transrectal ultrasonography was performed to verify ovulation and estimate corpus luteum (CL) volume immediately before AI (d 0) and on d 7 and 18 of the experiment. On d 19, 36 cows (18 cows/treatment; 2 cows/group) diagnosed without the presence of a CL on d 0 but with a CL greater than 0.38 cm(3) in volume on d 7 and 18 were slaughtered for collection of conceptus, uterine luminal flushing, and tissue samples from the CL and endometrium. Cows receiving CSSO had greater concentrations of linoleic and other omega-6 FA in plasma (P < 0.01), endometrium (P <= 0.05), CL (P <= 0.05), and conceptus (P <= 0.08) compared to CON. On d 7 of the experiment, CSSO-supplemented cows had greater plasma progesterone concentrations (P < 0.01) and CL volume (P = 0.02) compared to CON, whereas no treatment effects were detected (P >= 0.15) for these parameters on d 18 (treatment x day interaction; P < 0.01). Cows receiving CSSO tended (P = 0.09) to have greater concentrations of interferon-tau in the uterine flushing media compared with CON. However, no treatment effects were detected for mRNA expression genes associated with pregnancy establishment in endometrial, CL, and conceptus samples (P >= 0.12). In summary, supplementing beef cows with 100 g of CSSO beginning after AI favored incorporation of omega-6 FA into their circulation, reproductive tissues, and conceptus, without impacting expression of genes associated with pregnancy establishment on d 19 of gestation.
Keywords: beef cows; calcium salts of soybean oil; gene expression; interferon-tau; pregnancy; progesterone